Ecological Research on Endangered Medicinal Plants in Bromo Tengger Semeru National Park - SYAMSUL HIDAYAT; ROSNIATI A RISNA (Society for Indonesian Biodiversity, 2007)
An ecological research on some endangered medicinal plants in Ranu Pani, Senduro and Pronojiwo Resort, Bromo Tengger Semeru National Park, East Java was conducted on July 2006. Nine study areas were chosen inside the forest of national park and one site at the enclave area (non-forest area), covering a wide range of plant association, abundances, forest and habitat types, and altitudes. A systematic parallel line sampling method using quadrat technique was employed and total area sampled were 1 ha. The total of 13 medicinal plant species were found in quadrats and there were three species i.e. Euchresta horsfieldii (Lesch.) Benn., Cinnamomum sintocBl., and Alyxia reinwardtii Bl. known as endangered species which seemed to have a tendency for cluster distribution. Instead of being discovered inside the conservation area, an endangered species, Pimpinella pruatjan Molkenb., was found at an agriculture land in the adjacent area. The Shannon-Weaver diversity index was 1.10 with Evenness value of 0.99. Based on contingency table constructed from the sampling result, we found no single association between the endangered medicinal plant species. Habitat, conservation status andpotential threats of the four endangered species are also briefly described.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: endangered medicinal plant, ecology, diversity, conservation